2019
DOI: 10.14720/aas.2019.113.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in phosphorus nutrition of wheat plants grown in a calcareous sandy soil by incorporating chemical phosphorus fertilizer with some selected organic substances

Abstract: <p>Established fertilizer recommendations for wheat is urgently required to enhance the application efficiency of commercial phosphorus (P) fertilizers. This study evaluated the effect of inorganic P combined with some organic supplements i.e., citric acid (CA) or pigeon manure juice (PMJ), on alkaline-calcareous soil as well as plant measurements and phosphorus efficiency parameters of wheat (Triticum durum ’Boussalem’). Different concentrations of P in solution i.e., 0.05, 0.10, 0.15, 0.20, and 0.40 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The increase in wheat grain yield, biological yield, and straw yield with application of phosphatic fertilizers is in consistency with many research reports (Jahan and Amiri 2018;Mihoub et al 2019;Naeem et al 2013). P fertilization improves the quality and number of grains per spike which ultimately increase both straw and grain yield (Poulsen et al 2005).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The increase in wheat grain yield, biological yield, and straw yield with application of phosphatic fertilizers is in consistency with many research reports (Jahan and Amiri 2018;Mihoub et al 2019;Naeem et al 2013). P fertilization improves the quality and number of grains per spike which ultimately increase both straw and grain yield (Poulsen et al 2005).…”
Section: Discussionsupporting
confidence: 86%
“…Manzoor (2013) also reported that Langmuir model estimated lower P requirement under given soil and adsorption conditions. Soil solution P at the level of 0.2 mg P L −1 is sufficient for optimum yield (Naeem et al 2013;Mihoub et al 2019). Mihoub et al (2016) and Ayenew et al (2018) reported that several crops achieved maximum growth at 0.2 and 0.32 mg P L −1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations